Highly Efficient Uniaxial In‐Plane Stretching of a 2D Material via Ion Insertion. Issue 37 (31st July 2021) - Muscher, Philipp K.; Rehn, Daniel A.; Sood, Aditya; Lim, Kipil; Luo, Duan; Shen, Xiaozhe; Zajac, Marc; Lu, Feiyu; Mehta, Apurva; Li, Yiyang; Wang, Xijie; Reed, Evan J.; et al.
Abstract: On‐chip dynamic strain engineering requires efficient micro‐actuators that can generate large in‐plane strains. Inorganic electrochemical actuators are unique in that they are driven by low voltages (≈ 1 V) and produce considerable strains (≈ 1%). However, actuation speed and efficiency are limited by mass transport of ions. Minimizing the number of ions required to actuate is thus key to enabling useful "straintronic" devices. Here, it is shown that the electrochemical intercalation of exceptionally few lithium ions into WTe2 causes large anisotropic in‐plane strain: 5% in one in‐plane direction and 0.1% in the other. This efficient stretching of the 2D WTe2 layers contrasts to intercalation‐induced strains in related materials which are predominantly in the out‐of‐plane direction. The unusual actuation of Li x WTe2 is linked to the formation of a newly discovered crystallographic phase, referred to as Td', with an exotic atomic arrangement. On‐chip low‐voltage (< 0.2 V) control is demonstrated over the transition to the novel phase and its composition. Within the Td'‐Li0.5− δ WTe2 phase, a uniaxial in‐plane strain of 1.4% is achieved with a change of δ of only 0.075. This makes the in‐plane chemical expansion coefficient of Td'‐Li0.5−δ WTe2 far greater than of any other single‐phase material, enabling fast and efficient planar electrochemical actuation. Abstract : Ion insertion in between the 2D layers of WTe2 is shown to induce an exotic crystallographic phase. This novel phase is linked to uniquely large uniaxial in‐plane strain. On‐chip electrochemical control over the lithium content in single flakes of WTe2 is demonstrated as an efficient, fast, and reversible way to control the strain, making Li x WTe2 a promising microscale actuator.